2023
DOI: 10.1039/d2cc06257g
|View full text |Cite
|
Sign up to set email alerts
|

The molecular-level effect of alkoxide additives in iron-catalyzed Kumada cross-coupling with simple ferric salts

Abstract: The molecular-level role of alkoxide salts, used as alternative additive to N-methylpyrrolidone in iron-catalyzed alkyl-alkenyl/aryl cross-coupling reactions, is investigated. Detailed spectroscopic studies reveal that alkoxides promote the formation of homoleptic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The use of magnesium alkoxide salts, either as an ω-functionalization of the nucleophilic partner ( Scheme 4 ) or as an external molecular additive such as EtOMgCl ( Scheme 5 ), also likely proceeds similarly to the NMP, as demonstrated by recent studies by Neidig and Lefèvre ( Table 2 , entry 2) [ 38 ]. No alteration of the structure of the active species [Me 3 Fe II ] − is observed in the presence of an excess of EtOMgCl, suggesting that the alkoxide additives solely bind to the magnesium cations.…”
Section: Discussionmentioning
confidence: 91%
“…The use of magnesium alkoxide salts, either as an ω-functionalization of the nucleophilic partner ( Scheme 4 ) or as an external molecular additive such as EtOMgCl ( Scheme 5 ), also likely proceeds similarly to the NMP, as demonstrated by recent studies by Neidig and Lefèvre ( Table 2 , entry 2) [ 38 ]. No alteration of the structure of the active species [Me 3 Fe II ] − is observed in the presence of an excess of EtOMgCl, suggesting that the alkoxide additives solely bind to the magnesium cations.…”
Section: Discussionmentioning
confidence: 91%
“…4 Although the role of the alkoxide was not determined by Lefevre, the Neidig group recently described work seeking to uncover the impact of this additive. 9 Using freeze−trap Mossbauer and electron paramagnetic resonance (EPR) spectroscopies, it was shown that EtOMgBr as an additive led to similar speciation as to when NMP is employed. Importantly, the stability of the catalytically active [FeMe 3 ] − anion was shown to be reduced when EtOMgBr was used as an additive in place of NMP.…”
Section: Fe Catalysismentioning
confidence: 99%
“…Magnesium alkoxide additives were reported by Lefevre and co-workers as providing similar benefit to NMP . Although the role of the alkoxide was not determined by Lefevre, the Neidig group recently described work seeking to uncover the impact of this additive . Using freeze–trap Mossbauer and electron paramagnetic resonance (EPR) spectroscopies, it was shown that EtOMgBr as an additive led to similar speciation as to when NMP is employed.…”
Section: Fe Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of such compounds is moreover possibly carried out at a ton scale synthesis in our facilities, making it appealing for scalable processes. This functionalization enables a kinetic stabilization of organoiron­(II) species, which are key intermediates of the coupling process . Inspired by this previous work, we sought to develop a convenient synthesis of the sex pheromone of Spodoptera frugiperda relying on a key iron-catalyzed cross-coupling between 1 Z -hexenyl bromide ( 2 , readily obtained from pentanal 1 ) and a mixture of α,ω-difunctionalized Grignard reagents bearing terminal alkoxide groups ( 4 n =6 , 4 n =8 , and 4 n =10 , Scheme ).…”
Section: Introductionmentioning
confidence: 99%